2020
DOI: 10.1200/jco.2020.38.29_suppl.127
|View full text |Cite
|
Sign up to set email alerts
|

Survey of challenges in access to diagnostics and treatment for neuroendocrine tumor (NET) patients (SCAN): Global disparities in quality healthcare for NETs.

Abstract: 127 Background: Neuroendocrine tumors (NETs) are rare and complex neoplasms with increasing incidence and prevalence worldwide. SCAN assessed global delivery of healthcare to NET patients. This analysis focused for the first time on healthcare quality evaluation by economic areas–Advanced Economies (AE) and Emerging and Developing Economies (EDE) classification used as per the International Monetary Fund. Methods: During Sept-Nov 2019, NET patients and healthcare professionals (HCPs) completed an online surve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…Results: Six-hundred thirty patients were identified for the incidence analysis and 149 patients for prevalence and CSS analyses. MANEC-P incidence-rate (12) was 0.011/100,000 populations, significantly higher in male, black and peaked at 75-79-years of age and was highest in the Northeast region (0.013) and lowest in the Midwest (0.009) region ( P < 0.01). A decreasing trend in MANEC-P incidence was observed (average annual percentage change = -0.71), with a significant difference between 2001-2010 and 2010-2017 (7.89 vs -11.13, P < 0.05).…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Results: Six-hundred thirty patients were identified for the incidence analysis and 149 patients for prevalence and CSS analyses. MANEC-P incidence-rate (12) was 0.011/100,000 populations, significantly higher in male, black and peaked at 75-79-years of age and was highest in the Northeast region (0.013) and lowest in the Midwest (0.009) region ( P < 0.01). A decreasing trend in MANEC-P incidence was observed (average annual percentage change = -0.71), with a significant difference between 2001-2010 and 2010-2017 (7.89 vs -11.13, P < 0.05).…”
Section: Discussionmentioning
confidence: 90%
“…C-12 Urinary Neuroendocrine Neoplasms (NENs) Treated in the "Modern Era": A Multicenter Retrospective Review Bryan Khuong Le, 1 Patrick W. McGarrah, 2 Julia Whitman, 1 Alan Paciorek, 1 Nitya Raj, 3 Diane Reidy-Lagunes, 3 Haley Hauser, 3 Tiffany Le, 3 Jaydira Del Rivero, 4 Andrea Apolo, 4 Amr Mohamed, 5 David L. Chan, 6 Kathleen Batty, 6 Emily K. Bergsland, 1 Thorvardur R. Halfdanarson. Chunmei Bai, 1 Jianming Xu, 2 Lin Shen, 3 Jie Li, 3 Zhiwei Zhou, 4 Zhiping Li, 5 Yihebali Chi, 6 Xianjun Yu, 7 Enxiao Li, 8 Nong Xu, 9 Tianshu Liu, 10 Wenhui Lou, 10 Yuxian Bai, 11 Xianglin Yuan, 12 Xiuwen Wang, 13 Ying Yuan, 14 Jia Chen, 15 Sha Guan, 16 Songhua Fan, 16 Weiguo Su. 16 Background: Two previous phase 3 studies (NCT02589821, NCT02588170) have demonstrated surufatinib significantly improved progression-free survival compared with placebo in patients with advanced pancreatic neuroendocrine tumors (NETs) and extrapancreatic NETs.…”
Section: C-11 Lurbinectedin In Extrapulmonary Metastatic Neuroendocri...mentioning
confidence: 99%
See 3 more Smart Citations